Smart glasses for remote assistance: analysing usability and optimal user characteristics among young adults with and without autism. - Osman, Raneen; Lamash, Liron (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: Young adults with autism spectrum disorder (ASD) often face challenges achieving independence and require ongoing support from caregivers. Smart glasses can develop skills and provide remote support, but user discomfort suggests further investigation into their usability and suitability. Materials and methods: This study assesses smart glasses' usability, comparing young adults (20–34 years) with (n = 22) and without (n = 22) ASD performing an online shopping task (OST). It explores correlations between usability and users' cognitive, sensory and emotional characteristics. Assessments included demographics, Adolescent/Adult Sensory Profile, Behaviour Rating Inventory of Executive Function-Adult (BRIEF-A) and Depression and Anxiety Stress Scale (DASS) and post-task, the Usefulness, Satisfaction and Ease-of-Use (USE) and Post-Study System Usability Questionnaire (PSSUQ). Results: Findings showed good usability for both groups (PSSUQ M = 2.82; USE M = 5.29; SD = 0.81). The ASD group showed more difficulty in the ease-of-use category. Sensory characteristic correlations were found between the USE usability score and low registration (r = −0.40, p = 0.01) and between the PSSUQ and low registration (r = 0.34, p < 0.05), seeking (r = −0.35, p < 0.05) and sensitivity (r = 0.35, p < 0.05). Correlations were found between PSSUQ and BRIEF-A for cognitive (r = 0.36, p < 0.05) and PSSUQ and DASS for emotional (r = 0.30, p = 0.05) characteristics. Cluster analysis identified a subgroup (n = 19; 43.2%) more suited for smart glasses, with higher seeking behaviours and executive functions, lower sensitivities and negative emotional states. Conclusions: Findings highlight smart glasses' potential for providing remote support. Implications for Rehabilitation: Enhancing Autonomy through Remote Support Smart glasses can effectively provide remote assistance for young adults with autism spectrum disorder (ASD), helping them perform daily tasks independently. This technology can also be used in rehabilitation to promote autonomy and reduce reliance on in-person support. Tailoring Technology to Individual Needs The usability of smart glasses is influenced by the user's sensory, cognitive and emotional characteristics. Rehabilitation professionals should consider these differences when implementing smart glasses in therapeutic settings to optimise user experience and task performance. Potential for Broader Application Beyond ASD, the findings indicate that smart glasses can benefit a wide range of populations with diverse rehabilitation needs. By offering hands-free support and enhancing interaction with the environment, this technology can be tailored to individual requirements, improving engagement and outcomes in the rehabilitation process.